2023
DOI: 10.3390/su15043337
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Modeling of the Kobo-Golina River in the Data-Scarce Upper Danakil Basin, Ethiopia

Abstract: A proper understanding of hydrological processes is vital for water resource assessment, management, and conservation at a local, national, and global scale. The role of hydrological models is critically important in rarely studied ungauged catchments including of Kobo-Golina, in the Danakil basin of Ethiopia. The main objective of this research is to model the hydrology of the Kobo-Golina catchment using the completely restructured SWAT (SWAT+) model. Validated reanalysis river flow from the Global Flood Awar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…As a surrogate for AET, remotely sensed data were used. Remote-sensingbased AET estimates from the Moderate-Resolution Imaging Spectrometer (MOD16 AET) and the Food and Agricultural Organization of the United Nations (FAO) portal (water productivity open access portal, WaPOR) have been widely used as options to calibrate and validate hydrologic models in Ethiopia [58][59][60][61] and other countries [62,63]. For this study, we used WaPOR as it offers continuous actual evapotranspiration data across Africa and the Middle East at three spatial resolutions (250 m, 100 m, and 30 m).…”
Section: Climate Datasetsmentioning
confidence: 99%
“…As a surrogate for AET, remotely sensed data were used. Remote-sensingbased AET estimates from the Moderate-Resolution Imaging Spectrometer (MOD16 AET) and the Food and Agricultural Organization of the United Nations (FAO) portal (water productivity open access portal, WaPOR) have been widely used as options to calibrate and validate hydrologic models in Ethiopia [58][59][60][61] and other countries [62,63]. For this study, we used WaPOR as it offers continuous actual evapotranspiration data across Africa and the Middle East at three spatial resolutions (250 m, 100 m, and 30 m).…”
Section: Climate Datasetsmentioning
confidence: 99%
“…For the period 2005–2010, this methodology of calibration led to an increase in skill of the simulation of monthly river discharge compared to observations. Abate et al (2023) also found positive results by using GloFAS hydrological reanalysis and actual evapotranspiration (AET) from Moderate Resolution Imaging Spectroradiometer (MODIS) to calibrate the SWAT model for the ungauged Kobo‐Golina catchment in Ethiopia. Alternatively, hydrological reanalyses can be used to extend existing observational records (Mbuvha et al, 2022) creating a longer record on which to calibrate hydrological models.…”
Section: Examples Of Applications Of Global Hydrological Reanalysismentioning
confidence: 99%
“…To date, SWAT+ has been applied mostly in the United States, Africa [6][7][8][9][10], Europe [1,3,[11][12][13], and in some watersheds in Asia [14,15]. Examples of SWAT+ applications include determining the impact of climate change on water and sediment yield [2,9,11,16], hydrological mass balance calibration and reservoir representation [6], and reproducible model studies [17].…”
Section: Introductionmentioning
confidence: 99%